PENDAMPINGAN DAN PELATIHAN PEMANFAATAN MEDIA E-COMMERCE PADA PENGRAJIN TAPIS LAMPUNG DI DESA RAJABASA LAMA KECAMATAN LABUHAN RATU KABUPATEN LAMPUNG TIMUR - Ermanita Pematasari; Siti Kholijah; Siti Fatimah (LPPM STAI DARUSSALAM LAMPUNG, 2022)
ABSTRAK Tapis cloth is a traditional clothing of the Lampung tribe in the form of a sarong made of woven cotton yarn with motifs such as natural, flora and fauna motifs. Tapis cloth is made of woven cotton yarn with a willing motif or decoration, silver thread or gold thread with an embroidery system. The materials used are sanwos or woven fabrics, cotton threads and gold or silver threads, and pempek. Community Service Activities carried out by the STAI Darussalam PKM Team in Lampung were carried out in Rajabasa Lama Village, Labuhan Ratu District, East Lampung Regency, which is one of the typical Lampung filter fabric craftsman villages that still uses traditional manufacturing techniques. Which so far, is still marketed traditionally at a fairly low price. This causes less than optimal marketing. The research approach used in this community service is participation-based research known as Participatory action research (PAR). Community Service Activities, starting from FGDs, Training and Assistance in the Utilization of E-Commerce, which are carried out are not only limited to carrying out one of the Tridharma of Higher Education, but together with community groups can provide the widest possible benefits to the community, namely the results of filter crafts from the village. Rajabasa Lama can be better known by the wider community so that it can increase sales results and can contribute to improving the community's economy.